2000
DOI: 10.1128/jb.182.5.1432-1436.2000
|View full text |Cite
|
Sign up to set email alerts
|

Novel Missense Mutations That Affect the Transport Function of MalK, the ATP-Binding-Cassette Subunit of the Salmonella enterica Serovar Typhimurium Maltose Transport System

Abstract: We report on novel mutations in the malK gene of Salmonella enterica serovar Typhimurium, encoding the ATPase subunit of the maltose transporter (MalFGK 2 ). Biochemical analysis suggests that (i) L86 might be involved in a signaling step during substrate translocation and (ii) E306 may be critical for the structural integrity of the protein.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
18
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 21 publications
1
18
0
Order By: Relevance
“…Suppressor mutations in malK that restore transport were selected from these maltose-negative mutants, and they mapped mainly in the helical domain of MalK, consistent with the idea that the EAA regions constitute a recognition site for the helical domains of ABC ATPases. The proximity of residues in the EAA motifs of MalF and MalG to MalK was further confirmed through crosslinking experiments (215). The hypothesis that the EAA motif constitutes a site of interaction between the IM proteins and the conserved ABC modules (89, 244) is clearly proven correct by structural studies (205,285,343,366).…”
Section: Bpd Uptake Systemsmentioning
confidence: 54%
“…Suppressor mutations in malK that restore transport were selected from these maltose-negative mutants, and they mapped mainly in the helical domain of MalK, consistent with the idea that the EAA regions constitute a recognition site for the helical domains of ABC ATPases. The proximity of residues in the EAA motifs of MalF and MalG to MalK was further confirmed through crosslinking experiments (215). The hypothesis that the EAA motif constitutes a site of interaction between the IM proteins and the conserved ABC modules (89, 244) is clearly proven correct by structural studies (205,285,343,366).…”
Section: Bpd Uptake Systemsmentioning
confidence: 54%
“…This notion is further supported by the following experimental evidence; when mutated to phenylalanine the residue immediately succeeding Ala-85 in MalK, Leu-86 causes a defective transport complex. Biochemical analysis revealed that the purified variant exhibits ATPase activity comparable to wild type, whereas the transport complex containing the mutant MalK fails to hydrolyze ATP in the presence of maltose-loaded binding protein (38). Thus, the mutation is likely to interrupt the signaling pathway by preventing activation of the ATPase activity of the MalK subunits.…”
Section: V114c and V117c Formed Cross-links Only With Malf(s3c)/malg(ϫ)-mentioning
confidence: 99%
“…Other candidate residues for which conformational changes have been demonstrated are located in the helical subdomain of MalK (24,31) and in the LSGGQ motif (32).…”
mentioning
confidence: 99%